Pengawasan Pemerintah Daerah Terhadap Aktivitas Bengkel Umum Kendaraan Bermotor - Toisuta, Gerick M; Bakarbessy, Andress Denny; Nirahua, Garciano (PATTIMURA Law Study Review, 2025)
In this industry. The study also identifies various challenges faced in the implementation of supervision, including lack of technical knowledge among workshop owners, limited resources to conduct routine supervision, and low awareness of the importance of regulatory compliance among industry players. Through a normative approach, this study recommends the need for increased cooperation between the government and the private sector to develop training programs for technicians and workshop owners, as well as stricter law enforcement against regulatory violations. In addition, socialization regarding consumer rights and obligations and the importance of safety standards in workshop services is also considered important to increase public awareness. With these results and recommendations, it is hoped that the supervision of public workshops for motor vehicles can be more effective, which will ultimately improve the quality of service and protect consumers, as well as.